2002
DOI: 10.1111/j.1530-0277.2002.tb02551.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Systemic Alcohol and Central Nicotine Administration into Ventral Tegmental Area on Dopamine Release in the Nucleus Accumbens

Abstract: These data support the hypothesis that the reinforcing effects of ethanol are at least partially mediated through the nicotinic receptors in the VTA. Furthermore, administration of selective nicotinic antagonists may be of therapeutic potential in reducing the rewarding effects of ethanol. The data also suggest that the combined effects of ethanol and nicotine on the "reward pathway" may be a contributing factor to the high incidence of smoking in alcoholics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(63 citation statements)
references
References 50 publications
5
57
0
1
Order By: Relevance
“…17). ACh levels in the ventral tegmental area are increased in highbut not low-ethanol consuming rats (28), and the nonselective nAChR antagonist mecamylamine decreases ethanol consumption in high-alcohol-preferring rats (20,21) and blocks ethanolinduced dopamine release (21,23,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17). ACh levels in the ventral tegmental area are increased in highbut not low-ethanol consuming rats (28), and the nonselective nAChR antagonist mecamylamine decreases ethanol consumption in high-alcohol-preferring rats (20,21) and blocks ethanolinduced dopamine release (21,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The nAChRs are well characterized ligandgated ion channels that, in addition to mediating the rewarding properties of nicotine, also regulate several central functions, such as memory and attention, sleep and wakefulness, anxiety and pain (19). The nAChRs have received little attention despite evidence that they play a role in the development of alcohol dependence.Studies have shown that the nonselective nAChR antagonist, mecamylamine, decreases ethanol consumption in rats (20)(21)(22) and attenuates ethanol-induced dopamine release in the nucleus accumbens (21,23,24). Furthermore, mecamylamine has been reported to block the stimulant or euphoric subjective effects of alcohol and decreases the self-reported desire to consume more alcohol in healthy human volunteers (25-27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the different peptide systems may be involved, the strongest available evidence is provided by studies of the mesolimbic dopaminergic system showing nicotine and ethanol to have both additive and synergistic effects on mesocorticolimbic DA signaling. This has been revealed using systemic administration of nicotine plus accumbal administration of ethanol, which together increase DA levels in the accumbens to a greater extent than administration of either drug alone (Tizabi, Bai, Copeland, & Taylor, 2007; Tizabi, Copeland, Louis, & Taylor, 2002). Nicotine and ethanol are also found to act synergistically when administered directly into the posterior VTA, where the mixture of these two drugs as compared to either alone produces a greater change in gene expression in mesolimbic DA neurons (Truitt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Varenicline, the 4 2 nAChR partial agonist, has been found to decrease alcohol consumption and alcohol-seeking behavior in an animal model [308]. In addition to behavioral assays, neurochemical studies suggest that mecamylamine attenuated ethanolinduced extracellular DA levels in the mesolimbic system of rats and mice [306,[309][310][311][312][313]. Furthermore, pretreatment or intra-VTA perfusion of mecamylamine reduces voluntary alcohol-intake and preference in alcohol preferring rats [310,314].…”
Section: Alcoholismmentioning
confidence: 96%